The meltdown - Kinney, Jeff (New York : Amulet Books, 2018)
"When snow shuts down Greg Heffley$1 (Bs middle school, his neighborhood transforms into a wintry battlefield. Rival groups fight over territory, build massive snow forts, and stage epic snowball fights. And in the crosshairs are Greg and his trusty best friend, Rowley Jefferson"--Amazon.s
Keywords: Schools -- Juvenile fiction; Best friends -- Juvenile fiction; Snow -- Juvenile fiction; Diaries -- Juvenile fiction